(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of mild ovarian stimulation protocols in women with diminished ovarian reserve at the IVF Center of Hong Ngoc General Hospital from January 1, 2024 to November 30, 2024 and to analyze factors associated with the outcomes of mild stimulation protocols in this patient group at the same center and during the same time period. Method: This was a retrospective study based on patients’ medical records. Results: The study showed that the use of a mild stimulation protocol in patients with diminished ovarian reserve, with a mean age of 37.7 years, resulted in an average total FSH dose of only 401.6 IU over an average of 8.8 days of ovarian stimulation. This yielded a mean number of 2.2 oocytes, with a maturation rate of 87.36% and a fertilization rate of 84.4%. On average, 1.1 embryos were transferred per cycle. The pregnancy rate was 29.45%, implantation rate 21.4%, clinical pregnancy rate 22.7%, and biochemical pregnancy rate 6.7%. No cycles were canceled due to lack of follicular growth, and no cases of ovarian hyperstimulation syndrome were reported. Conclusion: With a reasonable success rate, the mild stimulation protocol offers an attractive alternative for patients with diminished ovarian reserve compared to conventional IVF protocols. It provides favorable outcomes with a reasonable duration of stimulation and, notably, requires a minimal amount of exogenous FSH, thus significantly reducing treatment costs.